Avaliação de uma nova fonte de fósforo sobre desempenho, qualidade de carne e expressão gênica em frangos de corte - Oliveira, Armando de Amorim (2024)
This study aims to evaluate the effects of a new phosphorus source on zootechnical performance, meat quality, blood parameters, and gene expression of calcium (Ca) and phosphorus (P) transporters in broilers from 1 to 42 days of age. For this purpose, 400 mixed-sex Cobb broilers were used, distributed into 2 treatments (dicalcium phosphate (DP) and tricinophos (TRIC)) in a completely randomized design with 10 replicates containing 20 birds each. Zootechnical performance data were collected weekly, and at 42 days of age, 6 birds from each treatment were slaughtered by CO2 stunning followed by exsanguination and blood collection for biochemical analysis. The pectoralis major muscle was also collected for meat quality analysis, and jejunal tissue was collected for gene expression analysis of Ca and P transporters. A significant difference (p<0.05) was observed in feed intake from 1 to 21 days of age, with birds receiving the TRIC diet consuming less feed and showing similar feed conversion to those on the DP diet. Birds fed the TRIC diet had lower cooking loss (23.0% vs 28.67%), higher water retention capacity (13.16 vs 10.39), higher pH value (6.1 vs 5.5), and in color evaluation, a higher a* value (1.19 vs 0.85) and b* value (3.14 vs 2.57). Meat tenderness in relation to birds fed DP was evidenced by firmness (53.36 vs 73.18; P = 0.0006) and chewiness (101.77 vs 136.26; P = 0.0108) results. Biochemical analyses showed that birds fed TRIC had higher activity of creatine kinase (CK) (61368 vs 4110.0) and alkaline phosphatase (AP) (3203.0 vs 1663.6) than birds fed DCP. In the gene expression evaluation, it was observed that calbindin (CALB1) had higher expression in birds with TRIC as the phosphorus source in their diet. According to the results of this study, birds fed the TRIC diet showed similar or superior performance to those fed DP, in addition to having more tender meat, better chewiness, elasticity, and lower liquid loss during cooking.